Dynamic Characterization Of Engine Mount At Different Orientation Using Sine Swept Frequency Test. - Mohd Ripin, Zaidi; Ooi, Lu Ean (2010)
Rubber engine mounts are commonly used to provide vibration attenuation. The loss factor and dynamic stiffness of engine mount provide fundamental information of the energy dissipation.